DEVELOPMENT OF VIRTUAL LABORATORY MEDIA ASSISTED BY CONSTRUCT2 SOFTWARE IN BIOLOGY LEARNING - M. Noris; Sulistyo Saputro; Muzzazinah Muzzazinah (EDUSAINS, 2022)
The construct2 software is an HTML5 based Game Builder Tool. Construct2 can be used in the development of application-based learning media such as a virtual laboratory (VLab). This study aims to determine the effectiveness of virtual laboratory media assisted by construct software2. This type of research is research and development (R&D). The data analysis method is in the form of media validation data based on experts, the results of the virtual laboratory media feasibility test and the results of the learning media effectiveness test. This type of research is research and development (Research and Development) which is accommodated from Sugiyono (2008) which was developed according to the conditions and situations. This type of research is research and development (Research and Development) which is accommodated from Sugiyono (2008) which was developed according to the conditions and situations. The stages of development according to Sugiyono are: (1) Identification of potential and problems, (2) Data collection, (3) Product design, (4) Design validation, (5) Design revision, (6) Product testing, (7) Revision product. , (8) Use trial, (9) Product revision, and (10) Mass production. The results of the research are application-based virtual laboratory applications that can be programmed using Construct2 or HTML5 software. The results of the validity test according to experts ranged from 97%, while the exact location was 87%. The implications of the research are expected to contribute to researchers, practitioners, to be able to optimize constructions in creating 3-dimensional virtual laboratory media.